EFFECT OF NEEMTA 2100 TOXICITY ON ACETYLCHOLINESTERASE AND SERUM GLUTAMATE OXALOACETATE TRANSAMINASE ENzynms IN SERUM OF FISH, OREOCHROMIS MOSSAMBICUS - Parveen, Mahira; Sharma, Ritu; Kumar, Santosh (Journal of Indian Fisheries Association, 2015)
Acetylcholinesterase and Serum glutamate oxaloacetate transaminase enzymes have been used as marker monitoring the effect of neem seed based pesticide Neemta 2100 on the fish, Oreochromis mossambicus. Fishes exposed to sublethal concentrations of neemta 2100 for acute periods of 24 and 48 hours were sacrificed to determine enzyme activities in serum affected due to toxicity. Laboratory studies of in vivo exposure of this pesticide showed synergistic inhibitory effect during acute period of toxicity. Acetylcholinesterase was noticed as 6.25 J.Uil substrate hydrolyzed I mg protein I hour and Serum glutamate oxaloacetate transaminase was noticed as 36.71 J.Uil substrate hydrolyzed I mg protein I hour in control fish serum. Significant decrease in GOT level in Neemta 2100 treated fishes after short term exposure indicated its severe toxicity to fish. Key words: Serum, Neemta 2100, Enzymes, Fish